baikal region - Grigoryeva, Elena (project baikal, 2021)
All happy families are alike, every unhappy family is unhappy in its own way. Leo Tolstoy, “Anna Karenina” Despite the recent rearrangement of the federal districts, the notion “Baikal Region” still exists. The three subjects of the Russian Federation, Zabaikalsky Krai, the Buryat Republic and the Irkutsk Region are united around the lake, which is often called “Great Sea”. This region is our journal’s homeland. The journal’s regional section contains the materials that show typical problems of provincial cities and their solutions. The disunity of citizens and the lack of social communication constitute a key problem that gives rise to a lot of other problems. The project for public spaces in Shilka became the winner of the Federal Competition for Formation of a Comfortable Urban Environment. It is the third annual issue of the Competition organized by the Ministry of Construction, and the level of the projects is trending upward. Another winner of this year is a project for Tulun. The problem related to the flood of 2019 and the wave of social pessimism and depression caused by it is to be solved by the project. Deprived areas with a high level of crime draw urbanists’ attention all around the world. Studying the case of Novo-Lenino in Irkutsk, F. Kudryavtsev and E. Tokareva raise a question about the ways of rehabilitation for the neighborhood. The threats to the cultural and historical heritage compose a complex problem, where developers’ immediate interests, unfair expert reviews, the bureaucracy’s short-term vision, citizens’ indifference etc. are tightly interwoven. However, the story about fighting for the protection of one of Irkutsk’s historic buildings inspires hope and optimism.